Conversion of carbon dioxide and methane to syngas over Ni/SiO2 catalyst prepared from waste palm oil fuel ash - Hazirah A., Razak; Nornasuha, Abdullah; J., Gasang; Herma Dina, Setiabudi; Chin, S. Y.; Nurul Aini, Razali (IOP Science, 2019)
Carbon dioxide (CO2) reforming of methane (CH4) over nickel (Ni)-supported SiO2 catalyst is a greener approach as this pathway transforms greenhouse gases into gas energy. SiO2 support was synthesized from waste palm oil fuel ash (POFA) with different Ni loading (Ni/SiO2). The SiO2(POFA) was synthesized by drying the treated POFA overnight and calcined at 600°C for 6 h. The Ni/SiO2 (POFA) catalyst with different Ni loading were synthesized by impregnation method. The physicochemical properties of the Ni/SiO2 (POFA) were characterized using nitrogen adsorption-desorption, x-ray diffraction (XRD), and fourier transform infrared (FTIR) spectroscopy. The catalytic performance of the Ni/SiO2 (POFA) was carried out at 800°C and atmospheric pressure with CO2/CH4 feed ratio of 1/1. The SiO2 (POFA) possess a good support material as it has a high surface area 6.95 m2 g−1 and assist well dispersion of Ni as evidenced by BET analysis. Higher catalytic activity was achieved at 53.10% of CO2 conversion and 67.6% of CH4 conversion over 5Ni/SiO2 (POFA). However, lower CO2 conversion of Ni/SiO2 (POFA) catalyst was due to the larger particle size of Ni and weak metal-support interaction in Ni/SiO2 (POFA). This finding proved that the waste POFA can replace the commercial SiO2 for catalytic gas reaction and solve the environmental problem.